ENVIRONMENTAL PERFORMANCES OF AGRICULTURE IN THE EUROPEAN UNION COUNTRIES - Ilić, Ivana; Krstić, Bojan; Jovanović, Sonja (Economics of Agriculture, 2017)
The strong impact of agriculture on the environment has caused the integration of environmental objectives into the Common Agricultural Policy. In parallel with the development of CAP, attempts have been made to make agricultural production more ecologically oriented. The subject of this paper explores the environmental performance at the level of the European Union, with special emphasis on the environmental performance of the agriculture. The environmental performances of agriculture will be analyzed on the basis of the data on Environmental Performances Index (EPI) for the issue area – Agriculture. The aim of this research is to classify the European Union countries into homogenous groups according to the level of achieved environmental performance of agriculture.